HUBUNGAN AKTIVITAS KERJA KELOMPOK DENGAN PRESTASI SISWA KELAS VIII DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SEKOLAH MENENGAH PERTAMA ISLAM TERPADU AL-WASHLIYAH 20 MEDAN TAHUN AJARAN 2019/2020 - Fahri, Muhammad Agus (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
In the components of the elements of education, one of the most important is students, where each student has an important role and responsibility to lead to and become a student with a level of maturity both in terms of cognitive, affective and psychomotor. With the existence of good student activities including doing well in group work, the quality of achievement that will be obtained will be achieved properly. Students who do well in group work will better understand the material being studied, it will result in the formation of high learning achievement for the students themselves. Based on the preliminary study that the author conducted, it was found that there were still students who were not able to move and be active in group work properly. The symptom is that there are still students who do not have good material preparation or study material to be done in group work, there are still students who cannot answer questions in group work activities and there are still students who have not been able to make conclusions after their group work is complete. To make it easier for the authors to examine the problems above, the authors formulate the problem, namely whether there is a significant relationship between group work activities on students' learning achievement of Islamic Religious Education and the factors that influence it. . This study uses two variables, namely the variable x (Group Work Activity) and the variable y (Student's Islamic Religious Education Learning Achievement). To find out the two data, the writer used a questionnaire, interview and documentation. Because the research data is interval data, the collected data will be analyzed using the "product moment". Based on the author's research, it can be concluded that there is a significant relationship between group work activities and the achievement of grade VIII students in the Islamic religious education subject at the integrated Islamic junior high school al-washliyah 20 Medan in the 2019/2020 academic year.